PENGARUH MEDIA PEMBELAJARAN AUDIO VISUAL KETERAMPILAN FOREHAND DRIVE TENIS MEJA PENJAS FKIP UNTAN 2016 - Anggraini, Atika; Triansyah, Andika; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out how the influence of audio visual media on forehand table tennis skills on student PENJAS FKIP UNTAN 2016. This research method using experimental method with experimental design with pretest-postest design one-group descriptive quantitative design. The sample used is 20 subjects. Sample collection technique with saturated sampling. The data collection tool used is a test for a table tennis forehand for 3x30 seconds. Data analysis is used with manual calculation system. The result of the research is the lowest score of 15 and the highest score is 40 with mean (average) 28,87, then subject is given treatment that is by audio visual media and pengurungan method that is drill, after subjected to subject test in retest with post-test that is get the lowest score 50 and the highest score is 90 with mean (mean) 71.175. Having done t-test t arithmetic ≥ t table 31.62 ≥ 1.729 at level 0.05 means there is a difference between pre-test and post-test. The effectiveness of high audio visual media (ES = 4.3). Based on these results the use of audio visual media is very significant to forehand table tennis skills on students FKIP UNTAN 2016.  Keywords: Media, Audio-Visual, Forehand Drive